ANALISIS GAYA BELAJAR SISWA KELAS V SD N 79 KECAMATAN SUKAJADI KOTA PEKANBARU - Dini Fransiska Putri; Syahrilfuddin Syahrilfuddin; Muhammad Fendrik (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The background of this research is that most of students do not know their own learning style yet. This reasearch aims to describe visual, auditory, kinesthetic learning style (VAK) and the tendency of fifth grade. The subject of this research is fifth grade. The grounded qualitative of theory approach was used to develop the theory inductively. The data was collected by deep interview role observation and document study. The data was analyzed by using Miles and Huberman analysis technique by gathering, reducing, applying, and drawing conclusion. The study result shows that fifth grade learning style is the combination of VAK learning style. The composition and learning style trend of students are different. From 9 studetns who became the subject research, there are 6 students tended more on kinesthetic, 2 students more on auditory learning style, and 1 student tending more on visual learning style.Key Words : learning style, elementary students